Successful studies as a requirement for the right to maintenance of adult single sons - Rivas Figueroa, Sacha Félix (2020)
This article is about the interpretation of the successful studies of a profession or trade regulated in the article 424 of the Civil Code as a presupposition of the right to maintenance of single sons (or single daughters) with legal age. For this, it starts from an analysis and understanding of the concepts and foundations of the right to maintenance, the law, Comparative Law, jurisprudence and all the presuppositions that set up this case regulated in order to propose an objective criterion as an interpretive parameter of what we should understand by “success in studies”.